Comparison of the frequency of loss‐of‐function LZTR1 variants between schwannomatosis patients and the general population. Issue 7 (14th April 2022) - Deng, Fanxuan; Evans, D. Gareth; Smith, Miriam J.
Abstract: Schwannomatosis is a rare tumor predisposition syndrome that causes multiple schwannomas. Germline loss‐of‐function (LoF) LZTR1 variants were only recently identified as disease‐causing, so relatively few variants have been identified in patients. In addition, many LoF variants exist in Genome Aggregation Database (gnomAD) in people who do not have clinical symptoms of schwannomatosis. These factors, and the incomplete penetrance seen in this condition, hinder definitive interpretation of the clinical significance of novel LoF variants identified in schwannomatosis patients. We collated published LOF LZTR1 variants identified in schwannomatosis patients and classified them according to current American College of Medical Genetics and Genomics/Association for Molecular Pathology/Association of Clinical Genomic Science guidelines. Subsequently, pathogenic/likely pathogenic schwannomatosis‐associated LoF variants were compared with LoF LZTR1 variants reported in gnomAD data. Using current classification guidelines, 64/71 LoF LZTR1 variants reported in schwannomatosis patients in the literature were classified as pathogenic/likely pathogenic, and their frequency in probands 64/359 (17.8%) was significantly higher than the frequency of potential LoF variants identified in the general population (0.36%; p < 0.0001). The majority of published classifications of schwannomatosis‐associated LoF variants are robust. However, the high frequency of LoF LZTR1 variants in the general population suggests that LZTR1 variants confer a reduced risk of schwannomas compared to germline NF2 and SMARCB1 pathogenic variants, making classification of novel variants challenging. Abstract : Loss‐of‐function (LoF) LZTR1 variants have been associated with schwannomatosis. However, many LoF LZTR1 variants exist in Genome Aggregation Database (gnomAD) in people who do not have clinical symptoms of schwannomatosis. We show here that LoF LZTR1 variants are strongly enriched in schwannomatosis patients, but the high frequency of LoF LZTR1 variants in gnomAD data suggest a reduced risk of schwannomas in comparison to other schwannoma predisposing genes.